Infrared thermography as option for evaluating the treatment effect of percutaneous transluminal angioplasty by patients with peripheral arterial disease - Staffa, Erik; Bernard, Vladan; Kubicek, Lubos; Vlachovsky, Robert; Vlk, Daniel; Mornstein, Vojtech; Bourek, Ales; Staffa, Robert (Vascular, 2017)
Aim of this study was to evaluate the possible use of infrared thermography as a supplementary method to the ankle-brachial index used in assessing the treatment effect of percutaneous transluminal angioplasty. The study included 21 patients, mean age was 60.22 years. Healthy control group included 20 persons, mean age was 55.60 years. Patients with symptomatic peripheral arterial disease (Fontaine stages I-III) were admitted for endovascular treatment by percutaneous transluminal angioplasty. Thermal images and ankle-brachial index values were obtained before and after treatment by percutaneous transluminal angioplasty. Median temperature change in the treated limb was 0.4℃, for non-treated limb was -0.5℃. The median value of ankle-brachial index in the treated limb increased by 0.17 from 0.81 after the procedure. The median value of ankle-brachial index in the non-treated limb decreased by 0.03 from the value of 1.01. Significant difference between treated limb and non-treated limb in change of ankle-brachial index was found with p value = .0035. The surface temperature obtained by the infrared thermography correlates with ankle-brachial index. We present data showing that the increase of ankle-brachial index is associated with increase of skin temperature in the case of limbs treated by percutaneous transluminal angioplasty. Our results also suggest potential of the use of infrared thermography for monitoring foot temperature as a means of early detection of onset of foot ischemic disorders.
Keywords: dospělí; Female; Regional Blood Flow; Skin Temperature; Adult; Peripheral Arterial Disease; výsledek terapie; ženské pohlaví; infračervené záření; Predictive Value of Tests; prediktivní hodnota testů; průchodnost cév; termografie; lidé; tlakový index kotník-paže; Ankle Brachial Index; balónková angioplastika; studie případů a kontrol; Aged, 80 and over; Infrared Rays; Treatment Outcome; Body Temperature Regulation; onemocnění periferních arterií; Middle Aged; prospektivní studie; Male; Case-Control Studies; Aged; Prospective Studies; Vascular Patency; regionální krevní průtok; lidé středního věku; senioři nad 80 let; termoregulace; senioři; mužské pohlaví; Thermography; Angioplasty, Balloon; dolní končetina; Lower Extremity; teplota kůže; Humans